2003
DOI: 10.1046/j.1442-2026.2003.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Documentation and tagging of casualties in multiple casualty incidents

Abstract: The use of triage tags is widely advocated as a tool to improve the management of multiple casualty incident scenes. However, there are no published reports to suggest that triage tags have improved the management of incidents involving more than 24 persons, and a number of reports have detailed problems associated with triage tag use. Alternative systems of scene management such as geographical triage have been successfully used in very large incidents, and are recommended as an alternative to triage tags. Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The time used filling in tags soaked in blood may be better utilized caring for severely injured patients. If the situation allows documentation, existing ambulance reports should be utilized to ensure familiarity and avoidance of tags containing information of little value [23]. In our study only 27% had access to triage tagging equipment and only 48% confirmed the existence of a system for major incident triage.…”
Section: Discussionmentioning
confidence: 71%
“…The time used filling in tags soaked in blood may be better utilized caring for severely injured patients. If the situation allows documentation, existing ambulance reports should be utilized to ensure familiarity and avoidance of tags containing information of little value [23]. In our study only 27% had access to triage tagging equipment and only 48% confirmed the existence of a system for major incident triage.…”
Section: Discussionmentioning
confidence: 71%
“…Then red patients with solved ABC compromise. All these patients will have red tags [ 22 ]. Next will be patients with single neurological disability, and finally those needing hospital evaluation but without any of the mentioned situations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 It has even been postulated that triage tags should be abandoned in favour of other triage methods. 8 However, this study only looked at comparing tags and determining whether any individual tag was superior to the others, not whether triage tags were useful in the triage process.…”
Section: Discussionmentioning
confidence: 99%